THE ESTIMATION OF INFORMATION VALUE OF CERTAIN FACTORS IN THE FORMATION OF ALLERGOPATOLOGY OF THE RESPiRATORY TRACT IN ADOLESCENTS - E. A. Abramatets; N. V. Efimova (Acta Biomedica Scientifica)
The prevalence of the bronchial asthma (BA) and the perennial allergic rhinitis (CAR), according to the questionnaire and medical examination, adolescents living in the industrial center of Irkutsk region, was 68 ± 3,4 per 100 patients. The most informative factors were: a positive skin prick test, detectable by skin testing, frequent respiratory infections in the history of passive smoking and family history.